STUDY OF HYBRID VIGOR, COMBINING ABILITY AND SOME GENETIC PARAMETERS IN OKRA. - Maha. M. Habib,; Kadhim D. H. Al-Jubouri, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed ot investigate, hybrid vigor and combining ability in some traits of okra.  to during  2021 and 2022 seasons, at private field located in the Mahmoudiya district of Baghdad, using the 7-line × 3 tester method. In the second season, the genotypes (parents and hybrids) were compared  in varietal trait  using  Randomized Complete Block  Design ( RCBD) with three replications. The results revealed significant differences among the parents and crosses for most of studied traits. Hybrids O4×O2 and O10×O3 emerged as standouts, achieving the highest yield in the  plastic house, with yields 927.80 kg and 892.60 kg, respectively. Hybrids O5×O1, O6×O2, and O8×O3 produced the highest numbers of pods. Hybrid O4×O2 exhibited the most significant positive values for hybrid vigor, reaching 54%, in plastic house yield. Certain parents exhibited a positive and significant general combining ability in the desired direction for the measured traits. Furthermore, hybrids O4×O2 and O10×O3 demonstrated a positive and significant specific combining ability in plastic house yield.